Антология выдающихся достижений в науке и технике. Часть 38: Лауреаты Нобелевской премии по физике за 2005 - 2010 гг. - Баранов, М.И. (Електротехніка і електромеханіка, 2017)
Приведен краткий аналитический обзор выдающихся научных достижений ученых мира, отмеченных Нобелевской премией по физике за период 2005-2010 гг. В число таких достижений вошли создание квантовой теории оптической когерентности, развитие лазерной точной спектроскопии, открытие чëрнотельной формы спектра и анизотропии космического микроволнового фонового излучения, открытие эффекта гигантского магнетосопротивления, открытие механизма спонтанного нарушения симметрии в субатомной физике, разработка новой технологии передачи света в оптических волокнах, изобретение полупроводниковой схемы для регистрации изображений и результаты новаторских экспериментов по исследованию двумерного материала графена. Наведено короткий аналітичний огляд основних наукових досягнень вчених світу, які відмічені Нобелівською премією по фізиці за період 2005-2010 рр. До числа таких досягнень увійшли створення квантової теорії оптичної когерентності, розвиток лазерної точної спектроскопії, відкриття чорнотільної форми спектру і анізотропії космічного мікрохвильового фонового випромінювання, відкриття ефекту гігантського магнетоопору, відкриття механізму спонтанного порушення симетрії в субатомній фізиці, розробка нової технології передачі світла в оптичних волокнах, винахід напівпровідникової схеми для реєстрації зображень і результати новаторських експериментів по дослідженню двовимірного матеріалу графена Purpose. Implementation of brief analytical review of the distinguished scientific achievements of the world scientistsphysicists, awarded the Nobel Prize in physics for period 2005- 2010 yy. Methodology. Scientific methods of collection, analysis and analytical treatment of scientific and technical information of world level in area of modern theoretical and experimental physics. Results. The brief analytical review of the scientific openings and distinguished achievements of scientists-physicists is resulted in area of modern physical and technical problems which were marked by the Nobel Prizes in physics for the period 2005-2010. Originality. Systematization is executed with exposition in the short concentrated form of the known scientific and technical materials, devoted creation of quantum theory of optical coherentness by scientists-physicists, development of laser exact spectroscopy, opening form of spectrum for a black body and anisotropy of space microwave base-line radiation, opening of effect of giant magnetoresistance, opening of mechanism of spontaneous violation of symmetry in subatomic physics, development of new technology of transmission of light in optical fibres, invention of a semiconductor circuit for registration of images and results of innovative experiments on research of 2D material of graphen. Practical value. Popularization and deepening of scientific and technical knowledges for students, engineers and technical specialists and research workers in area of modern theoretical and experimental physics, extending their scientific range of interests and collaboration in further development of scientific and technical progress in human society